The importance of the nutrition professional in guiding vegetarian practitioners (Research, Society and Development, 2021)
Introduction: In the field of vegetarian food, several differences in this practice can be identified. The term vegetarianism itself refers to a diet free from animal meat. General Objective: This article is part of a research that aims to show the different aspects of the practice of veganism and vegetarianism, their impact on health, and the influence of nutritionists in this practice. As well as describing the nutrients in the food composition and recommendation in the vegetarian diet. Methodology: The work was developed with data collection from secondary sources, through a bibliographic survey and based on the study of authors and their research on vegetarianism and its impact on human health. Results and discussion: To carry out this study, the impact of this type of diet in adult life was developed based on the articles. These researches were carried out on the basis of scientific articles, academic publications and scientific journals, in most of the last 10 years. Academic and scientific books were also used as reference material. Conclusion: We conclude with this project to guide vegetarian individuals about the importance of a nutritionist when starting this type of diet, pointing out the risks of lack of information that can cause numerous eating disorders, such as nutritional deficiencies that can be supplied by both the diet, adapting the nutrients and respecting the recommendations when, and if necessary, to use the supplementation.